Electroconvulsive therapy (ECT) reduces suicidal behavior and suicide deaths: response to Naismith et al. - Kellner, Charles H.; Espinoza, Randall T.; Gligorovic, Predrag; Sartorius, Alexander (Psychological medicine, 2025)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS003329172510281X/resource/name/firstPage-pdf-S003329172510281Xa.jpg